Russia's transition process in the light of a rising economy: Economic trajectories in Russia's industry and agriculture - Peter Voigt; Heinrich Hockmann (The European Journal of Comparative Economics, 2008)
Over the recent years Russia has faced an astonishing economic growth, coinciding with the era of Vladimir Putin's presidentship. Accordingly, it is not surprising that commonly these rising economic trajectories are attributed to progress in terms of transition initiated and further triggered by Putin's government. This paper is trying to investigate empirically whether the current growth in Russia tends to be caused mainly by (1) success of transition or just by (2) favourable external circumstances such as rising prices for oil, gas, etc. Thus, analytically, progress in transition has been approximated by efficiency estimates, which are - from a theoretical point of view - expected to be rising in course of transition of a formerly planned economy towards a free market system. In order to capture potentially different trajectories of several sectors and regions industry and agriculture have been considered separately, each at regionally aggregated level over a period of 11 years. In general, little evidence of the anticipated rising trends could be found. Instead, notable ups, downs and divergences among regions and sectors were uncovered. According to this analysis, Russia's current growth rates cannot be attributed to general success of transition. Instead, besides reaping the benefits of favourable external circumstances at world markets, from an empirical point of view, scale effects and slightly rising productivity appear to be the main causes of the recent track record. Moreover, in the industry the trend is also triggered by technological progress, which may indicate the turnaround after a decade of decline and give a reason to believe in an initiation of a long-term growth process. Unfortunately, in agriculture little evidence for such a sustainable growth process was evident so far. In general, the inter-sectoral integration in Russia's economy seems to be still quite low.
Keywords: D24; O11; P27; 330; Russia; transition progress; sector / regional comparison; TFP; efficiency